Free Fatty Acid Concentration and Carboxy methyl cellulase Activity of Some Formulas of Protected Fat-proteins Tested In Vitro - Hartati, Lilis; Agus, Ali; Yusiati, Lies Mira; Widyobroto, Budi Prasetyo (ANIMAL PRODUCTION, 2015)
The aim of this study was to determine the levels of free fatty acids and carboxymethylcellulase activity (cmc-ase) activity of some protected fat-proteins base on in vitro Tilley and Terry method. Two sources of fat, i.e. crude palm oil and fish oil and three sources of protein i.e. skim milk, soybean flour and soybean meal were used in the formulation of protected fat-protein, and thus there were six treatment combinations. The filtrate from the in vitro test was analyzed for the levels of free fatty acids and cmcase activity. The result of this research indicates that different combinations of feed materials and fat give different content of free fatty acid in first stage and second stage in vitro, with the best results in the combination treatment of skim milk and palm oil that give the lowest result of free fatty acid concentration in fisrt stage in vitro (0.168%) and the highest result free fatty acid concentration in second stage in vitro ( 4.312%) . The activity of CMC-ase was not influenced by different sources of fat and protein. It can be concluded was that the protection of the combination between skim milk and CPO gives the highest protection results.